Building transnational networks : civil society and the politics of trade in the Americas - Von Bulow, Marisa (Cambridge : Cambridge University Press, 2010)
'Building Transnational Networks tells the story of how a broad group of civil society organizations came together to contest free trade negotiations in the Americas. Based on research in Brazil, Chile, Mexico, the United States, and Canada, it offers a full hemispheric analysis of the creation of civil society networks as they engaged in the politics of trade. The author demonstrates that most effective transnational actors are the ones with strong domestic roots and that'southern' organizations occupy key nodes in trade networks. The fragility of activist networks stems from changes in the domestic political context as well as from characteristics of the organizations, the networks, or the actions they undertake. These findings advance and suggest new understandings of transnational collective action'--
Pt. I. Civil Society Organizations and their Pathways to Transnationality -- Introduction -- Multiple pathways to transnationality -- Pt. II The Politicization of Trade -- The contentious nature of trade debates -- New regionalism in the Americas -- Pt. III The Dynamics of Networks -- Trade protest networks -- The origins and dynamics of trade challengers' networks -- Pt. IV. Organizational Pathways to Transnationality -- The creation and demise of transnational coalitions -- Diffusion and differentiation of national coalitions -- Pt. V. The Search for Ideational Pathways -- Alternatives for the Americas -- Transnational collective action in dynamic political contexts -- Conclusions : agency, networks, and collective action.
Includes bibliographical references (p. 235-249) and index.
Keywords: Free trade -- Social aspects -- America; Civil society -- America